1998
DOI: 10.1080/000163598422884
|View full text |Cite
|
Sign up to set email alerts
|

Physical, chemical, and histologic changes in dentin caries lesions of primary teeth induced by regular use of polyol chewing gums

Abstract: A previous clinical trial showed that long-term use of saliva-stimulating polyol (xylitol and sorbitol) chewing gums was associated with arrest of dental caries in young subjects. After a 20-22-month intervention (when the subjects were 8 years old), a total of 23 primary teeth with extensive dentin caries lesions whose surface in clinical examination was found to be totally rehardened (remineralized) could be removed because the teeth were near their physiologic exfoliation time. These teeth were subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…5,7 Others have suggested that dentin specimens be examined directly without ethanol dehydration. 3,6,15,16 Not only does the hardness of carious primary dentin differ (approximately 10-fold) when it is measured under hydrated and dehydrated conditions, but it is particularly higher in more-demineralized tissue. 17 Secondly, the load used in the microhardness test varied between studies, ranging from 1.5 gf (9.8 Â 10 À3 N) 6 to 500 gf (4.9 N).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…5,7 Others have suggested that dentin specimens be examined directly without ethanol dehydration. 3,6,15,16 Not only does the hardness of carious primary dentin differ (approximately 10-fold) when it is measured under hydrated and dehydrated conditions, but it is particularly higher in more-demineralized tissue. 17 Secondly, the load used in the microhardness test varied between studies, ranging from 1.5 gf (9.8 Â 10 À3 N) 6 to 500 gf (4.9 N).…”
Section: Discussionmentioning
confidence: 98%
“…4 Hardness testing is an indirect method of tracking changes in the mineral content of dentin, and several microhardness studies on dentin in arrested carious lesions have been published. 3,[5][6][7] Dentinal microhardness in those studies typically ranged in KHN from 25 to 65 (245 to 638 MPa). However, microhardness results from different studies cannot be compared directly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Xylitol is used as an alternative sweetener to sucrose for diabetic patients because of its equivalent sweetening power but fewer calories [2], and is possibly even anticarcinogenic because it inhibits the growth of oral bacteria [3]. Due to these properties, xylitol is used as a sweetener in food products such as chewing gum, candy, soft drinks, and personal health products such as mouth wash and tooth paste.…”
Section: Introductionmentioning
confidence: 99%